Coronary Artery Disease in Patient with An Anomalous Origin of Right Coronary Artery - D. Nugraheni, Winda; Meuthia, Feranti (Indonesian Health Journal, 2024)
Coronary artery disease (CAD) remains a leading cause of mortality and morbidity in developed countries. CAD is a pathological process characterized by the accumulation of atherosclerotic plaques in the epicardial arteries, both obstructive and non-obstructive. This study aims to investigate rare cases of anomalous right coronary artery arising from the left main coronary artery and its clinical implications for coronary artery disease (CAD). The research methodology involved clinical examinations, echocardiography, diagnostic coronary angiography, and computed tomography angiography (CCTA) to obtain a comprehensive understanding of this case. The research findings indicate severe stenosis in the proximal-mid left main coronary artery (LAD) and an anomalous origin of the right coronary artery (RCA) leading to lower-level stenosis. Percutaneous coronary intervention (PCI) on the proximal-mid LAD lesion resulted in significant improvement in the patient's condition. The implications of this research underscore the importance of a deep understanding of coronary artery anatomical variations for accurate diagnosis and appropriate management of CAD patients, especially in rare cases like this.